Assessment for learning instrumentation in higher education - Akib, Erwin (Canadian Center of Science and Education, 2015)
This study explains assessment for learning instrumentation, especially in higher education. The population of this study was 100 lecturers of the Muhammadiyah Makassar University, Indonesia. A total of 50 items from six construct were analyzed and used to determine the reliability and validity of the questionnaire. The result shows that the person reliability of the instrument of 100 people was 0.91. It showed that the person reliability is excellent, as well item reliability showed a valued 0.96, which can be categorized excellent. It suggests that the goals of assessment should be to encourage that universities are administered in a way that provides the most appropriate practice in developing teaching and learning process.